The genus Aspicolpus Wesmael, 1838 (Hymenoptera, Braconidae, Brachistinae) from China, with descriptions of four new species - Yan, Cheng-Jin; Wu, Qiong; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2020)
The species of the genus Aspicolpus Wesmael, 1838 (Hymenoptera, Braconidae, Brachistinae) from China are revised. Four new species, namely A. clypeconcavus Yan et Chen, sp. n., A. frontirugatus Yan et Chen sp. n., A. jilinensis Yan et Chen, sp. n., and A. striatus Yan et Chen, sp. n. are described and illustrated. A key to the Chinese species of the genus Aspicolpus is updated.